Clinical Study on the Application of Preserved Urethral Mucosa at the Prostatic Apex in Transurethral Plasmakinetic Resection of the Prostate - Liang, Jun-Qiang; Ma, Wang-Teng; Lu, Bin-Wei; Dai, Liang; Zhao, Yu-Ming; Zhang, Ji-Dong; Tian, Bao; Liu, Qing-Li (Frontiers in Surgery, 2022)
Objective To explore the differences in the clinical efficacy, complications, and safety of transurethral plasmakinetic resection of the prostate (PKRP) by the conventional approach versus the approach preserving the urethral mucosa at the prostatic apex in the treatment of benign prostatic hyperplasia (BPH). Methods A total of 90 patients with PKRP admitted to the First Hospital of Qinhuangdao from December 2018 to March 2021 were selected and divided into a control group (conventional PKRP, n = 45) and an observation group (PKRP with preserved urethral mucosa at the prostatic apex, n = 45). The clinical efficacy, safety, and sexual function of the groups were evaluated using the patients’ International Prostate Symptom Score (IPSS), quality of life (QoL), prostate volume, maximum flow rate (Qmax), post-void residual (PVR), blood loss, surgical resection efficiency, and surgical complication data. Results The differences in the preoperative indicators, glandectomy quality, and glandectomy rate between the groups were not statistically significant (P > 0.05). However, in the observation group, the surgery time and blood loss were significantly lower compared with the control group, and the resection efficiency was significantly higher, with statistical significance (P < 0.05). In the follow-up, one month after surgery, the IPSS and QoL were lower in the observation group than in the control group, and the differences were statistically significant (P < 0.05); three months after surgery, the PVR, IPSS, QoL, and Qmax scores were similar between the groups, with no statistical significance (P > 0.05). In terms of surgical complications, the incidences of urinary incontinence and other complications after catheter extraction were significantly lower in the observation group than in the control group, and the differences between the groups were statistically significant (P < 0.05). Conclusion Compared with conventional PKRP, PKRP with preserved urethral mucosa at the prostatic apex can lead to immediate urinary continence after catheter extraction, reduce intraoperative blood loss, and shorten the surgery time, thus improving the surgical efficiency.